2017
DOI: 10.1016/j.neurobiolaging.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic score prediction captures nearly all common genetic risk for Alzheimer's disease

Abstract: We estimate the maximum prediction accuracy for the risk of Alzheimer's disease based on disease prevalence and heritability of liability. We demonstrate that the recently reported AUC values for predicting of Alzheimer's disease using polygenic scores reach about 90% of the estimated maximum accuracy that can be achieved by predictors of genetic risk based on genomic profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 24 publications
4
129
1
Order By: Relevance
“…Remarkably, this actual AUC value is quite close to the upper limit AUCmax = 82% (95% C.I. = 78–85%) (68) that could be achieved given the genetic epidemiology of the disease, namely disease prevalence (2%) and SNP-heritability (24%) (69,70), indicating that the polygenic risk profiling captures the SNP-heritability very well and is quite suitable for AD genetic risk prediction.…”
Section: The Role Of Genetics In Precision Medicine For Ad – From Gensupporting
confidence: 65%
“…Remarkably, this actual AUC value is quite close to the upper limit AUCmax = 82% (95% C.I. = 78–85%) (68) that could be achieved given the genetic epidemiology of the disease, namely disease prevalence (2%) and SNP-heritability (24%) (69,70), indicating that the polygenic risk profiling captures the SNP-heritability very well and is quite suitable for AD genetic risk prediction.…”
Section: The Role Of Genetics In Precision Medicine For Ad – From Gensupporting
confidence: 65%
“…This demonstrates the increased power that can be realized using pathologically confirmed tissue in comparison to clinically defined samples. In a more recent study, Escott-Price et al (2017a) used a modified approach to calculate the maximum possible predictive power (AUC max ) thereby improving the AUC produced previously from a value of 78.2% to 82%. More recently, Escott-Price et al (2017b) have performed PRS analysis on pathologically confirmed samples and found improved scores compared with the previous study on clinically diagnosed cases (Escott-Price et al (2015)).…”
Section: Discussionmentioning
confidence: 99%
“…gene-based assays, implementing polygenic risk scoring for assessing AD onset risk, are currently in late stage clinical development. In particular, a 90% maximum prediction accuracy via polygenic risk scoring can be accomplished by predictors of genetic risk based on genomic profiles [76]. …”
Section: The Precision Neurology Paradigm In Alzheimer’s Diseasementioning
confidence: 99%